Good practices of efficient packaging waste management - Cristian Teodor; Carmen Lenuta Trică; Raluca Ignat; Raluca-Mihaela Drăcea (Amfiteatru Economic Journal, 2020)
In the current European context, member states have increasingly effective and efficient concerns in the field of sustainable waste management. To this effect, the European Commission has adopted a package of measures in order to stimulate Europe's transition to a circular economy, which first involves efficient waste management and the consolidation of good practices in the field. Thus, Romania will have to comply with the new European rigors and improve its own waste management system. This paper aims to identify and analyse a set of good practices in the field of packaging waste in order to design one that is suitable for Romania. These examples are national models for organizing the management of packaging waste through deposit or storage systems. The main objective of these systems is to increase the recycling rates of packaging waste in accordance with European requirements, as well as the sustainable development of the waste sector, without causing economic losses to any of the stakeholders, namely business, population, environment and public authorities. The paper intends to conceptualize a specific model for the Romanian economy, respectively a model of organization and operation of the deposit system in the field of packaging waste that could be used by the competent authorities and the business environment.
Keywords: Q56; R11; O35; 330; packaging waste; deposit system; good practices; deposit reimbursement mechanism; Romania